Raising awareness about microbial antibiotic resistance in undergraduate dental students: a research-based strategy for teaching non-laboratory elements of a microbiology curriculum - Veronica Veses; Maria del Mar Jovani-Sancho; Raquel González-Martínez; Isidoro Cortell-Ballester; Chirag C. Sheth (BMC Medical Education, 2020)
Abstract Background Resistance to antimicrobial agents has become a problem in modern society. Antibiotic resistant bacteria undermine the prevention and treatment of infections. Undergraduate dental students in Europe are required to receive information in aspects of microbiology relevant for dental practice, including oral microbial pathogens and resistance mechanisms against antimicrobial compounds. The objective of this study was to implement a research-based strategy to aid the understanding of the increase in antimicrobial resistance in undergraduate dental student training. The primary outcome of this project is the efficacious delivery of the learning objectives. Methods Ten volunteer undergraduate student “ambassadors” were recruited to manage the project with assistance from lead academics. Student ambassadors were a source of peer learning for their colleagues. The project consisted of three phases: Pre-project preparation (in which the ambassadors received special instruction and training); Practical experience (in which the ambassadors worked with volunteer student colleagues to carry out the project); Public presentation of results (in which ambassadors presented study results at a scientific conference of their choosing). Results A total of 1164 students volunteered for the project, corresponding to an average participation rate of 76.4% students per year of the course. Following final debriefing, student participants and ambassadors were strongly positive in their evaluation of the achievement of 8 key student learning objectives. The results demonstrate that most volunteers improved their knowledge related to antimicrobial resistance mechanisms in microbiology. Additional benefits of participation in this project included an improvement in dental knowledge and ethics in biomedical research for the student volunteers, whilst the student ambassadors reported improved knowledge about critical thinking and study design, as well as a deeper understanding about microbiological analysis methods. Conclusions To the best of our knowledge, this the first instance of the application of project-based methodologies to the teaching of a traditionally non-laboratory component of a subject taught in the dentistry curriculum. Results from both students and ambassadors highlighted the increase in dental knowledge and an increased awareness of antimicrobial resistance as the key outcomes of this project.